The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/nar/gkr435
|View full text |Cite
|
Sign up to set email alerts
|

Role for hACF1 in the G2/M damage checkpoint

Abstract: Active chromatin remodelling is integral to the DNA damage response in eukaryotes, as damage sensors, signalling molecules and repair enzymes gain access to lesions. A variety of nucleosome remodelling complexes is known to promote different stages of DNA repair. The nucleosome sliding factors CHRAC/ACF of Drosophila are involved in chromatin organization during development. Involvement of corresponding hACF1-containing mammalian nucleosome sliding factors in replication, transcription and very recently also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 66 publications
3
54
0
Order By: Relevance
“…Recent work reported that SMARCA5 is recruited to DNA damage sites (Erdel et al, 2010;Lan et al, 2010;Nakamura et al, 2011;Sánchez-Molina et al, 2011). Chromatin immunoprecipitation (ChIP) coupled to quantitative PCR (qPCR) confirmed these results by showing SMARCA5 and cH2AX accumulation at two different sites flanking AsiSI-induced DSBs on chromosome 1 and 22 (supplementary material Fig.…”
Section: Smarca5 Is Rapidly Recruited To Dsbsmentioning
confidence: 64%
See 2 more Smart Citations
“…Recent work reported that SMARCA5 is recruited to DNA damage sites (Erdel et al, 2010;Lan et al, 2010;Nakamura et al, 2011;Sánchez-Molina et al, 2011). Chromatin immunoprecipitation (ChIP) coupled to quantitative PCR (qPCR) confirmed these results by showing SMARCA5 and cH2AX accumulation at two different sites flanking AsiSI-induced DSBs on chromosome 1 and 22 (supplementary material Fig.…”
Section: Smarca5 Is Rapidly Recruited To Dsbsmentioning
confidence: 64%
“…1F; supplementary material Fig. S3C,D) (Erdel et al, 2010;Lan et al, 2010;Nakada et al, 2010;Sánchez-Molina et al, 2011). Nakamura and co-workers implicated a role for the RNF20 E3 ubiquitin ligase in SMARCA5 recruitment to DNA breaks (Nakamura et al, 2011), whereas, another report suggested a role for ACF1 in SMARCA5 recruitment to DSBs, although formally it was not shown that ACF1 loss abrogates SMARCA5 assembly at DSBs (Lan et al, 2010).…”
Section: Parp and The Recruitment Of Smarca5 To Dsbsmentioning
confidence: 98%
See 1 more Smart Citation
“…A structural role for KIF4 explains the previously reported activation of DNA damage signaling pathways in KIF4-null ES cells 14 likely brought about by replicationassociated defects in chromatin assembly. 32 In line with KIF4 mediated chromatin-associated S-phase defects, the observed chromatin phenotypes upon KIF4 loss are reminiscent of those seen in mutants of replication factors such as ORC2 or defective resolution of Holliday junctions in Bloom's syndrome cells. 33,34 The molecular interactions of chromokinesin KIF4 and the chromosome condensation and DNA replication machinery occur probably in the context of larger complexes since human KIF4A and condensin can be biochemically purified with condensin, the DNA methyltransferase DNMT3B, the chromatin remodelers SIN3A and hSNF2H and the histone deacetylase HDAC1.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, SNF2H interacts with CSB [97], and the ACF1 subunit is recruited to UVC-induced DNA damage [98]. Knockdown of the mammalian ISWI ATPase SNF2H/SMARCA5 or its auxiliary factor ACF1/BAZ1A also leads to mild UVC sensitivity [99]. However, further experimental evidence is required to understand how ISWI chromatin remodeling functions in the UVC-DNA damage response.…”
Section: Iswimentioning
confidence: 99%